Expert Answers
kingattaskus12 eNotes educator| Certified Educator

Move the minus sign from the denominator to the front of the expression.

`-5/3 * 4 * -(2)/(-9)`


Move the minus sign from the denominator to the front of the expression.

`-5/3 * 4 * (2/9)`


Multiply `-5` by `4` to get `-20` .

`-(20)/3 * (2/9)`


Multiply all the factors in `-5/3*4*(2/9)`

`(-20 (2/9))/3`


Multiply `-20/3`  by `2/9`  to get `-40/27`  

Thus, the answer is
`-40/27`  

baxthum8 eNotes educator| Certified Educator

`5/(-3)* 4* (-2)/ (-9)`

` ` `5/(-3)* 4/1* (-2) / (-9)`

` ` `(5*4*-2)/(-3*1*-9)`

`(-40) / 27`

The solution is `(-40)/27.`

sid-sarfraz | Student

QUESTION:-

5/-3 x 4 x -2/-9

ANSWER:-

`5/(-3)*4*(-2)/(-9)`

`=5/(-3)*4/1*(-2)/(-9)`

When there is a minus sign in the denominator of a fraction then the whole fractions sign turns into minus. Hence;

`=(-5/3)*4/1*(-2)/(-9)`

When a fraction contains minus signs in both numerator and denominator, both the signs will be canceled leaving a plus sign. Hence;

`=(-5/3)*4/1*2/9`

Now Multiply the fractions with positive signs that can be done easily.

`=(-5/3)*8/9`

`=-40/27`

Hence the answer to this problem is `-40/27`

``

malkaam | Student

`5/-3 * 4 * -2/-9` 

In order to simplify this we need to follow the order of operations, to do that the first step will be to multiply the numerators by one another and then the denominators by one another as well,

`5/-3 * 4/1 * -2/-9`

`20/-3 * -2/-9`

`20/-3 * 2/9`

`40/-27`

`-40/27 Answer.`

5/-3 x 4 x -2/-9

 simply change the 4 to 4/1 and then multiply the top sides together
and the bottom sides together to get
5*4*-2
----------
-3*1*-9
 
-40/27
atyourservice | Student

`5/-3 xx 4 xx -2/-9= -40/27`

``

xelina | Student

5/-3*4*-2/-9=5/-3*4/1*-2/-9

                    =5*-3*-2/-3*1*-9

                    =-40/27

                    =1.48148148

levvy | Student

5/-3*4*-2/-9

=5/-3*4*2/9

=20/-3*2/9

=40/-27=-40/27